Conformable Fractional-Order Modeling and Analysis of HIV/AIDS Transmission Dynamics - Esam Y. Salah; Bhausaheb Sontakke; Mohammed S. Abdo; Wasfi Shatanawi; Kamaleldin Abodayeh; M. Daher Albalwi (International Journal of Differential Equations)
The mathematical model of the dynamics of HIV/AIDS infection transmission is developed by adding the set of infected but noninfectious persons, using a conformable fractional derivative in the Liouville–Caputo sense. Some fixed point theorems are applied to this model to investigate the existence and uniqueness of the solutions. It is determined what the system’s fundamental reproduction number R0 is. The disease-free equilibrium displays the model’s stability and the local stability around the equilibrium. The study also examined the effects of different biological features on the system through numerical simulations using the Adams–Moulton approach. Additionally, varied values of fractional orders are simulated numerically, demonstrating that the results generated by the conformable fractional derivative-based model are more physiologically plausible than integer-order derivatives.